Purification and structure elucidation of a cyclodipeptide from Streptomyces cirratus IHBB 10198 isolated from a glacier near Kunzum Pass in the Indian Trans-Himalayas - Pal, M.; Kumari, A.; Chhibber, S.; Gulati, A. (Vietnam Journal of Science and Technology, 2026)
Streptomyces cirratus IHBB 10198 was isolated from a glacier in Lahaul-Spiti, located in Himachal Pradesh, India on yeast malt extract agar (YMEA). The isolate was identified as Streptomyces cirratus NRRL B-3250T based on 16S rRNA gene sequencing. Crude extract from the cell-free culture supernatant showed antibacterial activity against Gram-positive bacteria including Micrococcus luteus MTCC 2470, Bacillus subtilis MTCC 121, Staphylococcus aureus MTCC 96, Staphylococcus aureus MLS 16 MTCC 2940, Staphylococcus aureus MRSA ATCC 43300 and Gram-negative Klebsiella pneumoniae ATCC 43816. The crude extract also showed antibacterial activity against three out of thirty-three strains of Staphylococcus aureus from the clinical samples. The culture was subjected to twenty-five liters of large-volume culturing in tryptone soya broth (TSB). Cell-free supernatant was extracted twice with ethyl acetate, dried under vacuum, and then defatted. A cyclodipeptide, cyclo (L-Pro-L-Val) was purified from the culture crude extract by flash chromatography and preparative HPLC. Structure elucidation was done by mass spectrometry, FT-IR, and NMR. No antimicrobial activity was shown by purified cyclodipeptide like the crude extract. The lack of activity may be attributed to the presence of cis-trans conformers in the natural cyclodipeptide.